Pengaruh Proporsi Dewan Komisaris Independen dan Keahlian Keuangan Komite Audit terhadap Manajemen Laba pada Perusahaan BUMN yang Terdaftar di Bursa Efek Indonesia Tahun 2019-2023 - Daeli, Karolina; Deviani, Deviani (Universitas Negeri Padang, 2025)
This study aims to determine the effect of the proportion of independent commissioners and audit committee financial expertise on earnings management. The research was conducted at state-owned companies listed on the Indonesia Stock Exchange with an observation period of 2019-2023. The sampling method uses purposive sampling; the research sample consists of 24 companies listed on the IDX. Multiple Linear Regression Analysis as a data analysis technique. Research findings show that the variable proportion of independent board of commissioners has a negative influence on earnings management. Meanwhile, the audit committee's financial expertise variable has a positive influence on earnings management.